A systematic review of sex differences in concussion outcome: What do we know?. Issue 6 (18th August 2019) - Merritt, Victoria C.; Padgett, Christine R.; Jak, Amy J.
Abstract: Objective: The purpose of this review was to examine sex differences in concussion, or mild traumatic brain injury (mTBI) outcome, updating previous critical reviews of the literature. Method: Within adult human studies, we reviewed a wide range of concussion outcome variables: prevalence of concussion, injury characteristics, postconcussion symptom trajectories and psychiatric distress, neuropsychological performance, and neuroimaging findings. Sports-related concussion, civilian, and military samples were included in the review. Results: Given the robust concussion literature, there is a relative paucity of research addressing sex differences following concussion. The majority of available studies focused on sports-related concussion, with fewer studies targeting other civilian causes of concussion or military-related concussion in females. Prevalence of concussion was generally reported to be higher in females than males. Although symptom reporting largely showed a pattern for females to report greater overall symptoms than males, examining individual symptoms or symptom clusters resulted in mixed findings between the sexes. Neuropsychological studies generally showed females performing more poorly than males on measures of visual memory following concussion, though this finding was not consistently reported. Conclusion: Research examining sex differences in humans following concussion, in general, is in its infancy, and exploration of sex differences in studies outside of the sports concussion domain is particularly nascent. Given the increased prevalence of concussion and potential higher symptom reporting among women, ongoing research is necessary to better understand the role of biological sex on outcome following concussion. Understanding sex differences has important implications for assessment, management, and treatment of concussion.